Dešimtasis Lietuvos koloproktologų draugijos suvažiavimas - Samalavičius, Narimantas Evaldas (Lietuvos chirurgija, 2022)
The Lithuanian Society of Coloproctologists X triennial meeting with International Conference Mayo Clinic days in Vilnius, Lithuanian–Turkish session and The International Society of University Colon and Rectal Surgeons Session. Vilnius, May 12 - 13, 2022.